Influenza A virus production in a single-use orbital shaken bioreactor with ATF or TFF perfusion systems. Issue 47 (8th November 2019) - Coronel, Juliana; Behrendt, Ilona; Bürgin, Tim; Anderlei, Tibor; Sandig, Volker; Reichl, Udo; Genzel, Yvonne
Abstract: Driven by the concept of plug-and-play cell culture-based viral vaccine production using disposable bioreactors, we evaluated an orbital shaken bioreactor (OSB) for human influenza A virus production at high cell concentration. Therefore, the OSB model SB10-X was coupled to two hollow fiber-based perfusion systems, namely, tangential flow filtration (TFF) and alternating tangential flow filtration (ATF). The AGE1.CR.pIX avian suspension cells grew to 50 × 10 6 cells/mL in chemically defined medium, maintaining high cell viabilities with an average specific growth rate of 0.020 h −1 (doubling time = 32 h). Maximum virus titers in the range of 3.28–3.73 log10 (HA units/100 µL) were achieved, corresponding to cell-specific virus yields of 1000–3500 virions/cell and productivities of 0.5–2.2 × 10 12 virions/L/d. This clearly demonstrates the potential of OSB operation in perfusion mode, as results achieved in a reference OSB batch cultivation were 2.64 log10 (HA units/100 µL), 1286 virions/cell and 1.4 × 10 12 virions/L/d, respectively. In summary, the SB10-X bioreactor can be operated with ATF and TFF systems, which is to our knowledge the first report regarding OSB operation in perfusion mode. Moreover, the results showed that the system is a promising cultivation system for influenza A virus vaccine production. The OSB disposable bioreactor has the potential for simplifying the scale-up from shake flasks to the large-scale bioreactor, facilitating rapid responses in the event of epidemics or pandemics.